PEMBINAAN PNS DAERAH YANG DIPERBANTUKAN PADA SEKRETARIAT KPU - ', Oktaviyanus (Jurnal Ilmu Administrasi Negara, 2016)
Development of Regional Civil Servants Seconded To The Commission Secretariat. This study aims to determine the development of the Regional civil servants seconded to the Secretariat of the Commission of Riau Province. This study used qualitative methods, while the technique of collecting data using interviews, observation and discussion. Data were analyzed using an interactive model. The results showed that the formation of the civil servants seconded to the Secretariat of the Regional Commission Riau Province nearly nothing is done specifically. Inherent in the nature of coaching positions KPU Secretary of Riau Province.